Economic development and reform deepening in China - Chen, Jiagui (London ; New York : Routledge, 2016)
This book, together with Macro-control and Economic Development in China is a collection of papers written in recent years about maintaining economic growth, managing inflation, the relationship between growth and structural adjustment, control of price growth, maintaining stable economic development, and other relevant aspects of macro-control, economic development, and deepening reform. Chinese government adopts many of the recommendations put forward by the book.
OCLC-licensed vendor bibliographic record.
Keywords: Economic development -- China; China -- Economic policy -- 2000-; China -- Economic conditions -- 2000-; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Economics / Macroeconomics; BUSINESS & ECONOMICS / Development / Economic Development